Biofilmed biofertilizers: a novel technology for green agriculture - Swarnalakshmi, Karivaradharajan; Prasanna, Radha; Saxena, Anil Kumar (Indian Farming, 2015)
Biofilmed inoculants combine in themselves, useful traits of different microorganisms, leading to better persistence under harsh environmental conditions and improvement in crop growth and yields, besides sustained soil fertility. The synergy in properties can provide enhanced nutrient management and biological control leading to long term sustainable crop production using environmentally safe means, besides overcoming the hurdles posed in the widespread adoption of biofertilizers.